1981
DOI: 10.1152/ajpheart.1981.241.4.h513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased plasma viscosity and red blood cell aggregation on blood viscosity in vivo

Abstract: The effects of increased plasma viscosity and induced red blood cell (RBC) aggregation on apparent viscosity of blood in vivo in the skeletal muscle of the dog were studied. Apparent viscosity in vivo was determined in the isolated and vasodilated calf muscles of one hindlimb by comparing pressure-flow relationships for RBC suspensions with pressure-flow relationships for a Newtonian solution of known viscosity. RBC suspensions of increased plasma viscosity with and without RBC aggregation were obtained by sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The relation of whole blood viscosity to the microcirculation is under debate and should be discussed with caution [26], as it was demonstrated that the viscosity of whole blood tends towards the values of plasma viscosity in small capillary tubes [27,28]. Therefore, it is possible that plasma viscosity plays a major role in microcirculatory blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…The relation of whole blood viscosity to the microcirculation is under debate and should be discussed with caution [26], as it was demonstrated that the viscosity of whole blood tends towards the values of plasma viscosity in small capillary tubes [27,28]. Therefore, it is possible that plasma viscosity plays a major role in microcirculatory blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…An insidious problem with the use of dextrans is that they may interact with vessel walls and change the functional properties of the endothelium or cause changes in blood viscosity (Gustafsson et al, 1981;Pearson and Lipowsky, 2000;Bendayan, 2002;Gonzalez-Castillo et al, 2003;Tsai et al, 2003). Specifically, dextrans can bind irreversibly to the coronary vessel lumen in a mass-dependent manner and modulate coronary blood flow (GonzalezCastillo et al, 2003).…”
Section: Experimental Issues Related To Use Of Dextrans As Molecular mentioning
confidence: 99%
“…This phenomenon was known since long ago, but the relationship between the RBCs aggregation (as cause) and the increase of resistance disturbing the flow (as result) in microvessels was difficult to prove convincingly because some inevitable factors, such as the pressure gradient and/or the microvascular diameter changes, could always be involved in the living microvascular networks. The effect of the RBCs aggregation on blood flow was largely examined by infusing macromolecules, preferably dextran with high molecular weight, into isolated organs [60][61][62] and in patients with serum hyperviscosity syndrome [63,64]. Under these conditions it was difficult to prove whether the increased flow resistance was due to the RBCs aggregation itself or to the increased plasma viscosity.…”
Section: Rbcs Aggregation As a Factor Inevitably Disturbing Blood Flomentioning
confidence: 99%